Prática Profissional de um Formador de Professores e Professoras de Matemática na Universidade Rovuma-Moçambique: Um Estudo (Auto) Biográfico - Mboa, Oniva João (2024)
This Dissertation deals with Mathematics Education in the initial and continuing education of teachers in Mozambique. As a general objective, it seeks to understand, through the writing of “si”, the practices developed in the training processes of mathematics teachers and their implications in the professional constitution as a trainer in a perspective of critical mathematics education. The study is (self) biographical based on (self) training, in which I participate as a narrator and researcher assuming the memorial as procedures and interpreted through reminiscences-references. I present three axes for the interpretation process: (i) teacher training policy in Mozambique, its intertwining with training practices and processes-effect of the policy on the life and life of the teacher; (ii) processes of appropriation of the references and practices of the teacher training mathematics; (iii) different ways of teaching and learning and the process identity and professional constitution of the teacher training in mathematics. As theoretical support, we work with the contributions of Ole Skovismose and Paulo Freire, for studies on critical mathematical education, as well as Inês Ferreira de Souza Bragança, Maria Helena Menna Barreto Abrahão and Maria Isabel da Cunha, for theoretical-methodological discussion of (self) biographical studies and professional teaching development mediated by this perspective.. As main understandings of this process of analysis of experience we highlight: axis 1, the interferences of hegemonic/political elites in the approval of programs with a market dimension influence the teacher in the practice of banking education as a way to fulfill his teaching responsibilities. Axis 2: I consider professional development to the movement that the trainer carries out, being of research, interaction and valorization of other important knowledge for the profession that are constituted in a dynamic way through continuous/permanent training. In addition, it is important to consider identity construction and teaching professionalism as a process that occurs through the relational, didactic-pedagogical and sociocultural dimension that is acquired throughout the teacher's trajectory. Axis 3:I understand that there is no specific method for teaching mathematics, but this process will take place through the disclosure of the realities that are occurring in our practice through educational practices, highlighting the importance of the student's daily life to contextualize the contents, and of the dialogue and the reflective capacity of the teacher/trainer. Important to consider that throughout professional life it is important to analyze the practice in a critical, ethical and responsible way, mobilizing and producing plural, reflective, contextual and which result from learning situated in the practices of teaching and learning and becoming a teacher.